Underpinning Chinese international students’ stress and anxiety during the first wave of COVID-19 outbreak: The moderating role of wisdom - English, Alexander; Ding, Yaxin; Zhang, Qionghan; Kulich, Steve J. (Frontiers in Psychology, 2022)
During the first wave of the COVID-19 outbreak, the Chinese diaspora (especially Chinese international students were subjected to greater stress than others, because they were under pressure from both fear of infection and coping with acculturation (e.g., discrimination). Consequently, more research is needed to understand the anxiety induced by COVID-19 stresses on this specific cultural group. The main purpose of this study is to investigate the relationship between COVID-19 stress and individuals’ anxiety, and the moderating roles of Acceptance, Reframing, and Striving (ARS) coping, the family support coping strategy, and wise reasoning. To test our predictions, we collected data from 224 Chinese international students (CIS). Results indicated a strong and positive relationship between pandemic stress and anxiety. Surprisingly, both ARS and family support coping did not moderate the association between COVID-19 stress and anxiety. Instead, wise reasoning as a potential reflective coping strategy interacted with COVID-19 stress to predict anxiety. Specifically, wise reasoning predicted more anxiety when individuals perceived low-level of COVID-19 stress, however, such a relationship disappeared when individuals perceived a high-level of COVID-19 stress. These findings about wise-reasoning extends our understanding of wisdom and how it plays a role in the context of COVID-19.